2022
DOI: 10.7759/cureus.24203
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient Experiences in an Academic Hospital in Saudi Arabia

Abstract: Introduction Patient continuous assessment is an important component of patient-centered healthcare systems and requires the identification of the services and resources of these systems to ensure patient satisfaction. This study aimed to determine the factors that affect patient satisfaction, identify patients' unmet health care and informational needs, and suggest measures to fill these gaps in healthcare systems. Methods A cross-sectional study included 235 patients who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Another study conducted in Italy considered the relationship between disease complications of diabetic patients and patient satisfaction and found that physician empathy was significantly associated with clinical outcomes related to patient satisfaction [ 16 ]. The same results were reported in a recent study conducted among 235 patients admitted to the medical ward of an educational tertiary healthcare center in Jeddah, Saudi Arabia, which found that perceived improvement in the health status of the patients was significantly associated with their satisfaction [ 17 ]. In this study, the main reasons for visiting the ED were shortness of breath (SOB) (17.8%), followed by sprain/fracture (11.9%), abdominal pain during pregnancy (10.0%), allergy (9.82%), trauma/wound (9.4%), and inflammation (8.65%).…”
Section: Discussionsupporting
confidence: 80%
“…Another study conducted in Italy considered the relationship between disease complications of diabetic patients and patient satisfaction and found that physician empathy was significantly associated with clinical outcomes related to patient satisfaction [ 16 ]. The same results were reported in a recent study conducted among 235 patients admitted to the medical ward of an educational tertiary healthcare center in Jeddah, Saudi Arabia, which found that perceived improvement in the health status of the patients was significantly associated with their satisfaction [ 17 ]. In this study, the main reasons for visiting the ED were shortness of breath (SOB) (17.8%), followed by sprain/fracture (11.9%), abdominal pain during pregnancy (10.0%), allergy (9.82%), trauma/wound (9.4%), and inflammation (8.65%).…”
Section: Discussionsupporting
confidence: 80%
“… 13 Another study indicated that patients’ overall mean satisfaction rate was 65.4. 14 Moreover, an observational study reported that the satisfaction rate increased after postoperative surgery for function and shape by 21.5% and 31.3%, respectively. 15 Detailed findings for each article are presented in table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…More precisely, 5 of 11 studies revealed that the better communication interaction with patients, the higher the percentage of satisfaction is vice versa. 14 17–20 For instance, Abass et al reported that patients expressed satisfaction with the information about symptoms to observe after discharge and with medical follow-up care. However, the lack of information regarding a new medication’s negative effects left patients unhappy.…”
Section: Resultsmentioning
confidence: 99%
“…The administration of early patient-centered care courses during medical school and residency programs can tremendously increase patient satisfaction and improve healthcare outcomes. 19 , 20…”
Section: Discussionmentioning
confidence: 99%